PEMBERIAN DAN PENCABUTAN GRASI PERSPEKTIF HUKUM ISLAM - Husin Wattimena (IAIN Ambon, 2017)
As head of state, the President has the prerogative, in granting pardons to convicted, based on the explanation of Law No. 5 of 2010 on the Amendment of Law No. 22 of 2002 on clemency, that by Act No. 5 of 2010. According to Article 2 paragraph (3) of Law No. 5 of 2010 that clemency has been granted to the convict, if repeat his actions, not allowing the latter granted clemency. It became the basis, that a head of state can not revoke a pardon has been given to a convict. Meanwhile, according to Islamic law, the treatment of the convict pardon only applies to the penalty-diyat and qisas ta'zir, and does not apply to jarimah hudud. Victims, or their families may only grant pardons to legal sanctions in the form of qisas, or certain diyat. Nor can grant clemency to ta'zir sanctions, which have been decided by the judge to convict. Keywords: clemency, Law No. 5 of 2010, Islamic criminal law